2020
DOI: 10.1177/0031512520903907
|View full text |Cite
|
Sign up to set email alerts
|

Setting, Age, and Intensity Influence Responses to Exercise in Young Endurance Runners

Abstract: We investigated the effects of exercise setting (indoor treadmill vs. outdoor trail), age (17 middle school, 18 high school, and 13 college participants), and level of exertion (Borg Ratings of Perceived Exertion of 10, 12, and 16 on a 22-point scale) on young male endurance runners’ heart rate (HR), running speed, attentive focus, and affect. Three-way analyses of variance revealed that on the outdoor trail (vs. indoor treadmill), HR and speed were higher ( p < .001) and attentive focus was more dissociati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…Likewise, studies involving runners have shown different attentional focuses depending on the setting. Specifically, runners reported more dissociative attentive focus and lowered RPE in exercise settings that were considered more distracting (e.g., outdoor vs. indoor) (16)(17)(18). The interplay between exercise setting on RPE during AVRG participation has yet to be studied, but the effects of the virtual world could allow participants to partly dissociate from internal stimuli and focus on their digital surroundings (19).…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, studies involving runners have shown different attentional focuses depending on the setting. Specifically, runners reported more dissociative attentive focus and lowered RPE in exercise settings that were considered more distracting (e.g., outdoor vs. indoor) (16)(17)(18). The interplay between exercise setting on RPE during AVRG participation has yet to be studied, but the effects of the virtual world could allow participants to partly dissociate from internal stimuli and focus on their digital surroundings (19).…”
Section: Introductionmentioning
confidence: 99%
“…The outdoor environments that were in the trials encompassed rural areas situated amidst trees and fields, nature parks and forests that were occasionally located near bodies of water, ,,,, city parks with trees and some built features, , university campuses with plants and trees within view, outdoor athletic tracks, ,,, and mountain trails. , Nine studies simulated an outdoor, nature-based environment in the laboratory by showing video footage of nature reserves, botanical gardens, rural fields with cattle nearby and woods, or a forest ,,, to their participants. Two studies , used a head mounted display to create a “virtual nature” environment.…”
Section: Resultsmentioning
confidence: 99%
“…As regards the indoor environments, studies often used standard rooms ,, or indoor corridors not exposed to greenery, room viewing blank screens, ,,,,, gyms and fitness centers, ,,,,, ,,,,,,,,, physiology laboratories, ,,,,,,,, a shopping center, and underground hallways …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations